'I thought it was a song but it turned out to be a siren': civilian listening during wartime in Israel. Issue 2 (4th May 2021) - Wood, Abigail
ABSTRACT: From warning sirens to loud booms in the sky; from tweaked radio playlists to the silence of a military funeral, sound is central to the civilian experience of wartime in Israel. Drawing upon public discourse among Jewish-Israelis during periods of armed conflict with Hamas militants in Gaza during 2012 and 2014, this article explores practices of civilian listening and sounding during times of national emergency. More than just making the ears prick, wartime sounds are implicated in an assemblage of bodily action: stimulating the body to move, prompting vocal responses and serving as a focal point for conversation. Recent work in ethnomusicology has sought to theorise soundscapes and listening practices during wartime – yet most work to date has focused on combatants. Building on previous literature in sound studies and on civil preparedness, in this article I focus on wartime regimes of civilian listening, arguing that embodied listening and sounding practices index a reconfiguration of the relationship between the state and its citizens, characterised by mutually co-constructed vigilance, and articulating consensual models of disciplined citizenship that help to sustain collective resilience, yet which also reinforce ethnonational divisions in society and bolster neoliberal practices of securitisation.